PENGARUH PERTUMBUHAN DANA PIHAK KETIGA (DPK) DAN CAPITAL ADEQUACY RATIO TERHADAP RETURN ON ASSET - Sri Rahayu, Anisa; Indrawan, Andri; Sudarma, Ade (Universitas Muhammadiyah Palembang, 2021)
This study aims to determine the effect of the Capital Adequacy Ratio against Return on Assets. This research was conducted using quantitative methods with an associative approach. The population and sample in this study are the financial statements of conventional commercial banks for the 2015-2019 period. In this study sampling with purposive sampling technique. Data collection techniques used are secondary data. Data analysis techniques used are the classic assumption test, multiple linear regression analysis and hypothesis testing. The results showed that Third Party Funds had no effect on ROA. Capital Adequacy Ratio (CAR) has a significant effect on Return on Assets (ROA) partially on banks that listed on the Indonesia Stock Exchange. Return on Assets is influenced by the Capital Adequacy Ratio of 41.3%. and 58.7% were influenced by other factors not examined in this study.